Manajemen Hipotermia pada Pasien Cedera Kepala: Suatu Tinjauan Literatur - Ismail Fahmi; Amelia Ganefianty; Ely Nurachmah (FORIKES, 2019)
Head injury is a crucial public health problem and causes social and economic problems throughout the world. Increased brain blood volume associated with increased body temperature will increase intracranial pressure (ICP) and cause the brain at risk of other injuries. This paper aims to identify the effect of hypothermia management on head injury patients. This article was a review of literature from several data bases, Pubmed, EBSCO Host, Google scholar, and Web of Science. Article search was restricted from 2007 to 2018 using the keyword